The effect of phenotypic aging on the relationship between cancer history and mortality in US adults - Tao, Meng-Hua; Lin, Chun-Hui; Chuang, Shu-Chun; Su, Wan-Ting; Wu, Horng-Shiuann (Frontiers in Aging, 2026)
Cancer survivors may have an accelerated biological aging process compared to cancer-free individuals. In this study, we aimed to investigate associations between clinical measures of biological aging and mortality (all-cause, cancer, and cardiovascular disease [CVD]) and examine whether the association between cancer history and mortality is mediated by biological aging. Data from the National Health and Nutrition Examination Survey (NHANES) 1999–2010, with follow-up through 31 December 2019, were used. A total of 1,493 cancer survivors and 4,479 matched non-cancer individuals aged ≥20 years were included. Cox regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Biological age (BA) was measured by phenotypic age (PhenoAge) based on nine clinical biomarkers. The mediating effect of biological age was assessed using structural equation models with the bootstrapping method by estimating indirect (IE) and direct (DE) effects from cancer history to mortality. Compared to non-cancer individuals, cancer survivors had accelerated PhenoAge. The association between cancer history and all-cause mortality risk was partially mediated by PhenoAge acceleration (HRIE = 1.02, 95% CI: 1.01–1.03). Accelerated PhenoAge also partially mediated the association between cancer history and cancer-specific mortality (HRIE = 1.06, 95% CI: 1.01–1.18). In particular, PhenoAge acceleration mediated 15.5% and 24.1% of the associations of cancer history with all-cause and cancer-specific mortality, respectively. Our results highlight the importance of decelerating the biological aging process among cancer survivors, which may improve survivorship and long-term health in this population.